การพัฒนาแบบประเมินสมรรถนะพยาบาลวิชาชีพอุบัติเหตุ-ฉุกเฉิน โรงพยาบาลจุฬาลงกรณ์ - ฐิติพร ถนอมบุญ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purpose of this research was to develop and set standards for emergency nurse competency scale for King Chulalongkorn memorial hospital. The research was conducted in two main phases. The first phase was consisted of 2 steps. The first step was explore and to select the essential emergency nurses competency by using focus group of 10 expert emergency nurse. The second step was to construct the competency scale by developing behavior assessment, scaling with Rubric 5 point scales, testing the efficacy scale and test the quality of the competency assessment from by 1 nursing director and 5 expert emergency nurse, and 5 emergency nurses. The second phase was to set standard score by 10 expert nurses. The results are as follows:1. The emergency nurse competency scale for King Chulalongkorn memorial hospital consisted of 7 domains 57 items. The 7 domains are Triage consisting of 9 items, advanced life support consisting of 4 items, emergency and crisis nursing practice consisting of 20 items, law ethics and patient advocacy consisting of 5 items, communication consisting of 5 items, academic capacity of and quality improvement in accident and emergency nursing consisting of 8 items and characteristic consisting of 6 items.2. The testing results of quality of instrument are as follows; CVI is 0.99, inter-rater reliability is 0.97 and Hoyt’s Analysis of Variance is 0.99.3. The cutting point of emergency nurses competency scale in King Chulalongkorn memorial hospital is T 51.84 .